2018
DOI: 10.1190/int-2017-0001.1
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical sedimentary evidence from core 973-2 for methane activity near the Jiulong Methane Reef in the northern South China Sea

Abstract: The Jiulong Methane Reef, located on the northern slope of the South China Sea, is characterized by several features, such as bottom-simulating reflections and authigenic carbonates, which are indicative of methane seeps that are currently occurring as well as those that occurred in the past. However, to date, the effect that these methane seeps have on the sedimentary environment is not completely clear. To provide further insights into the biogeochemical processes involved in methane seeps, a 6.73 m piston c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The AMS 14 C dating results (Figure 2) of planktonic foraminifera at site 973-4 were collected according to Lin [47] and Pan [42]. The planktonic foraminifera ( N. dutertrei ) collected from 12 samples throughout the site yielded an inconsecutive sedimentary sequence, especially in Unit II.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The AMS 14 C dating results (Figure 2) of planktonic foraminifera at site 973-4 were collected according to Lin [47] and Pan [42]. The planktonic foraminifera ( N. dutertrei ) collected from 12 samples throughout the site yielded an inconsecutive sedimentary sequence, especially in Unit II.…”
Section: Resultsmentioning
confidence: 99%
“…Before analyzing the source of carbonate minerals in the site 973-4, the abnormal increase in carbonate content in the depth range of Unit II was analyzed (Figure 3). Some studies [42,46,48] have shown that foraminiferal assemblages in this cold seep site display high species abundance and diversity. A total of 9111 benthic foraminifera were obtained from 63 identified samples [48].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations